Evolution characteristics of under-expanded accompanying jet under extreme heat condition. (October 2022) - Xue, Xiaochun; Zhou, Shupei; Yu, Yonggang
Abstract: This work is focused to study heat and mass transfer characteristics as well as evolution mechism of the wake flow field of the aerodynamic vehicle (ADV) with base-bleed unit (BBU) under extreme heat condition. Here, we have used a new type of annular nozzle for BBU to improve the structure of the wake flow field and provide more mass and energy for the wake flow field. Based on H2 -CO reaction mechanism for the post-combustion from the base-bleed gas and supersonic inflow, numerical models of unsteady accompanying jet coupled with the burning of the propellant are established for annular and circular nozzles. Comparisons of chamber pressure and jet shape of computational results are done with experimental studies, and a reasonable match has been obtained in these comparisons. Further, an under-expanded supersonic annular jet with containing central jet develops into a subsonic annular flow, presenting some distinguishing features compared with the decay process of an under-expanded circular jet. The base pressure coefficient for the annular nozzle increases by 21.8% and the peak of average base temperature is improved by 15.4%, which means this new type of annular nozzle is more beneficial to the increase of heat energy and pressure of the ADV base.